Cold-pressed sesame seed meal as a protein source: Effect of processing on the protein digestibility, amino acid profile, and functional properties - Pacheco, Maria Teresa Bertoldo (2022)
Alternative protein sources for the human diet may help overcome the food security challenge for a growing population and its environmental impact. Edible oil extraction by-products are potential sources due to high protein content. This study characterized cold-pressed sesame seed meals about the proximate composition, antinutritional factors, amino acid profile and score, and in vitro protein digestibility (IVPD). A central composite experimental design supported evaluating the impact of cooking, microwave, and ultrasound on the nutritional quality of this meal. The raw sample presented 35% of protein and 89% of IVPD. Optimized conditions were 87.8 ºC, pH 8.0, and 37 min for all processes studied, increasing IVPD up to 95%. The treatments effectively reduced up to 55% trypsin inhibitor activity and 81% phytic acid content. Lysine was the only limiting amino acid before or after processing. Sesame seed by-product has high-quality protein and can be a plant-based source for food formulations.